One-year mirror-image study of the impact of olanzapine long-acting injection on healthcare resource utilization and costs in severe schizophrenia. (December 2018) - Fefeu, Mylène; De Maricourt, Pierre; Cachia, Arnaud; Hoertel, Nicolas; Vacheron, Marie-Noëlle; Wehbe, Elie; Rieu, Christine; Olie, Jean-Pierre; Krebs, Marie-Odile; Gaillard, Raphaël; Plaze, Marion
Highlights: We assessed olanzapine long-acting injections efficacy in severe schizophrenia. Of the 40 patients included, 32.5% had previously been treated by clozapine. Olanzapine long-acting injections significantly reduced average bed days and hospital admissions. Olanzapine LAI was not associated with a greater risk of adverse events except for PSDS. Abstract: Olanzapine long-acting injections (OLAIs) are often prescribed to patients with severe schizophrenia who are typically excluded from randomized clinical trials. To date, no mirror-image study has examined the impact of OLAIs on healthcare resource utilizations in these patients. We conducted a retrospective, one-year mirror-image study of OLAIs on 40 patients with severe schizophrenic disorder. Illness severity was defined by failure to respond to two sequential antipsychotics. Outcomes included: (i) healthcare resource utilizations via hospitalization admissions, bed days, outpatient visits, and inpatient service costs computations (ii) clinical efficacy through changes in the Brief Psychiatric Rating Scale (BPRS) and in the Clinical Global Impression-Schizophrenia Scale (CGI-SCH), and (iii) adverse effects. After one year, OLAIs were associated with significant decreases of 65.7%, 86.2% and 86.2% in hospitalization admissions, bed days, and inpatient service costs respectively. A significant mean change of −0.47 and −0.63 was determined the BPRS and the CGI-SCH scores, respectively. There were no significant differences in the number of outpatient visits and adverse effects, except for post-injection sedation/delirium syndrome whose incidence was 0.30% per injection. This mirror-image study provides the first evidence that prescribing OLAIs reduces in a cost-effective manner average bed days and hospital admissions in patients with severe schizophrenia.